THE GENRE OF HORROR IN LITERARY WORKS AND ITS DISTINCTIVE CHARACTERISTICS - Rustamova Shakhnoza Abdurakhimovna (TADQIQOTLAR.UZ, 2024)
Abstract: The genre of horror in literary works has mesmerized audiences over many generations, presenting an unparalleled and unsettling journey that delves into fundamental fears and anxieties. This article scrutinizes the distinct attributes of horror literature, investigating its inception, fundamental traits, and sustained appeal. By conducting a thorough examination of pertinent literature and analyzing prominent works of horror, this research elucidates the components that delineate the genre and bolster its enduring resonance with readers.